2011
DOI: 10.1128/aem.00129-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycoparasitism-Related Genes in Trichoderma atroviride

Abstract: A high-throughput sequencing approach was utilized to carry out a comparative transcriptome analysis of Trichoderma atroviride IMI206040 during mycoparasitic interactions with the plant-pathogenic fungus Rhizoctonia solani. In this study, transcript fragments of 7,797 Trichoderma genes were sequenced, 175 of which were host responsive. According to the functional annotation of these genes by KOG (eukaryotic orthologous groups), the most abundant group during direct contact was "metabolism." Quantitative revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 64 publications
6
77
0
Order By: Relevance
“…In a plate confrontation assay, another ABC transporter of T. atroviride, TA_289170, was slightly downregulated before physical contact with the host compared to the control samples. Interestingly, genes involved in transport and metabolism of secondary metabolites were shown to be downregulated during mycoparasitic interactions (355). No homologs of TA_289170 were predicted in the genome of T. reesei or T. virens.…”
Section: Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…In a plate confrontation assay, another ABC transporter of T. atroviride, TA_289170, was slightly downregulated before physical contact with the host compared to the control samples. Interestingly, genes involved in transport and metabolism of secondary metabolites were shown to be downregulated during mycoparasitic interactions (355). No homologs of TA_289170 were predicted in the genome of T. reesei or T. virens.…”
Section: Transportmentioning
confidence: 99%
“…Mycoparasitism-related genes of T. atroviride were identified in a comparative transcriptome analysis during confrontation of T. atroviride with R. solani (355). Two genes encoding sugar transporters (TA_133590 and TA_150280) were shown to be downregulated compared to control conditions, independent of physical distance.…”
Section: Mfs Transporters (Sugar Transporters/general Substrate Transmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive survey of Trichoderma genomes revealed the presence of three types of peptaibol synthetases: the long (18-20 modules), medium (14 modules), and short (7 modules) (30, 96). One of the most interesting findings driven by genomics was the ability of Tex2, the 14-module NRPS, to synthesize 11-and 14-residue peptaibols in T. virens (102), later confirmed in T. reesei (38). On the basis of sequence alignment and the absence of an 11-module peptaibol synthase in either of the genomes, module skipping is suggested to be the mechanism of synthesis of these two classes …”
Section: Mycoparasitismmentioning
confidence: 99%
“…Using a high-throughput transcriptome analysis, 175 genes from T. atroviride were identified that responded to the presence of R. solani. Strongly upregulated genes include swo1 and axe1 as well as genes encoding aspartyl protease PapA and a trypsin-like protease Pra1 (102).…”
Section: Mycoparasitismmentioning
confidence: 99%